(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
This study presents an analysis of the academic production regarding approaches related to sustainable fashion aimed at Basic Education. Garcia; Miranda and Costa (2022) argue that themes related to sustainability and fashion should be present in the classroom. The authors bring up the possibility of raising important questions about consumption and social awareness by bringing these issues to the school environment. Starting from the relevance of approaching this theme for the training of students, the idea is to carry out a survey in the Capes Bank of Theses and Dissertations (BTDC) and in the main journals in the field of education in order to show how this has been addressed. In proposals aimed at basic education. We defined as a temporal cut the works published in the last ten years. In this sense, we raised some questions that guided our study: How has the sustainable fashion theme been treated in academic research? Has the number of studies dedicated to these discussions been relevant in view of their importance? And finally, how are proposals for inserting this theme being implemented at the level of basic education? With regard to methodological aspects, the study is characterized as a qualitative bibliographic research. After carrying out the research, we can see that there is a relevant number of studies that address the theme of sustainable fashion, but few are specifically directed to the school context, which denotes the urgency of carrying out more studies at this level of education.